MON-906 MULTIPLE ENDOCRINE NEOPLASIA TYPE 2A: Familiar Case Report - Sousa, Barbara K P (J Endocr Soc, 2020)
Introduction: Multiple endocrine neoplasia type 2A (MEN 2A) is a autosomal dominant transmission inherited syndrome which oncogenesis is based on germline mutations with RET proto-oncogene function gain. Patients have medullary thyroid carcinoma (CMT) and some develop unilateral or bilateral pheochromocytoma and/or primary hyperparathyroidism, its frequency depends on the inherited RET mutation. We present a case of a mother and daughter with marfanoid habitus and MEN 2A syndrome confirmed by genetic analysis that identified mutation in the RET gene, codon 634.Clinical cases: 35-year-old woman with weight loss, sweating, nausea, hypertensive peaks, syncope episodes and marfanoid habitus, with plasma metanephrines 9.1nmol/L (RV<0.5), bilateral adrenal tumors on MRI (4.7x4.5x3.3 cm left adrenal and 7.4x7.3x6.3 cm) and MIBG scintigraphy high uptake bilateral, with diagnosis of bilateral pheochromocytoma. She also had calcitonin 49.40pg/mL (RV<6.4), calcium 11.9mg/dL (RV 8.6-10.2), PTH 372.7pg/mL (RV15-65) and cervical ultrasound (USG) with solid and hypoechogenic thyroid nodule, diagnosed with CMT and primary hyperparathyroidism with 6 possible parathyroid glands by SPECT CT scintigraphy. Genetic panel by NGS identify germline mutation in RET códon 634 - minsense mutation: c.1900T>C. The patient denied prior family history. In the familiar screening, her 18-year-old daughter has a marfanoid habitus, serum calcitonin 48.8pg /mL (RV<9.8), CEA 3.8ng/mL(RV<3.0), cervical USG shows a thyroid nodule of 0.7x0.5x0.5cm, solid, hypoechoic, with microcalcifications and a central compartiment lymph node, whose puncture calcitonin > 2000pg/mL and 118pg/mL, respectively. She features plasma metanephrines 0.5mmol/L (RV<0.5), normal plasma normetanephrines, MIBG scintigraphy and adrenal MRI without alterations and absence of primary hyperparathyroidism. She has the same mutation as her mother.Conclusion: Although rare, it is essential to know the clinical and laboratory changes in MEN 2A in order to enable early diagnosis and treatment. Also, investigate every first-degree relative is important so complications and mortality of this syndrome can be reduced.